Prophylaxis protects infants with congenital heart disease from severe forms of RSV infection: an Italian observational retrospective study - Chiara Ratti; Anna della Greca; Deborah Bertoncelli; Monica Rubini; Bertrand Tchana (BMC, 2023)
Abstract Background In children with congenital heart disease (CHD) respiratory syncytial virus (RSV) infection may have a severe course, with increased risk of morbidity and mortality, requiring hospital admission and intensive care. The aim of the present study was to evaluate the effect of prophylaxis with palivizumab in preventing RSV-associated hospitalization in infants with CHD. Methods We carried out an observational, retrospective study in a paediatric cardiology division at a secondary-care centre in Italy, extracting from the database children with CHD who, from November 2004 to March 2022, matched the criteria for palivizumab prophylaxis, to evaluate the hospitalization rate in CHD patients with and without palivizumab prophylaxis and their RSV-related hospitalization characteristics compared with a group of children without CHD and no other underlying clinical conditions (control group, CG), hospitalized for RSV infection. Results One hundred twenty-eight children with CHD were enrolled in the study, mainly (71.9%) with increased pulmonary flow, and received palivizumab prophylaxis. Twenty-seven received hospital care for bronchiolitis. Almost all CHD patients hospitalized for bronchiolitis (26 out of 27) received partial prophylaxis (≤ 3 doses). CHD patients with bronchiolitis stay longer in the hospital than control (14.4 ± 21.7 days vs 6.2 ± 2.3 days) some of which require intensive care (n = 4). Conclusions Our study provides evidence of the efficacy of palivizumab in protecting patients with hemodynamically significant CHD under the age of 2 years from RSV disease and its life-threatening complications. Reducing hospitalisation rate, morbidity, and mortality in this category of patients, passive immune prophylaxis with palivizumab may impact healthcare resource availability and utilisation.